6 Cortical hypoperfusion on intensive care unit admission identifies the development of acute kidney injury. The microshock renal study. Issue 5 (26th September 2022) - Watchorn, Jim; Huang, Dean; Bramham, Kate; Hutchings, Sam
Abstract : Background: UK Defence has a vested interest in shock resuscitation and has limited access to renal replacement therapy. The aetiology of acute kidney injury (AKI) as a component of multiorgan failure is unclear and experimental data is conflicting. Clinical evidence is equally limited and novel methods of assessing the kidney in critical illness are needed. We assessed renal perfusion in septic shock using a novel method of contrast enhanced ultrasound (CEUS). Methods: Longitudinal observational study of 50 patients at four timepoints commenced within 24 hours of admission, two of the groups were defined retrospectively by the occurrence or absence of severe AKI. Contrast ultrasound was administered by infusion with subsequent replenishment kinetics. Renal artery Doppler ultrasonography, transthoracic echocardiography, sublingual video microscopy and biomarkers were measured to determine macro-haemodynamics, the severity of tubular damage and AKI subphenotype. Identical observations were performed in healthy controls, the third group. The primary outcome was the cortical perfusion differences between groups. Secondary outcomes were perfusion differences between subphenotypes, correlation of renal and sublingual microcirculatory perfusion and the differences in renal and global macro-haemodynamics. Results: Patients with septic shock have reduced cortical perfusion in comparison to healthy controls (average cortical mean transit time (mTT) 13.6s vs 2.2s p<0.0001) and patients who develop severe AKI have reduced perfusion from admission to ICU in comparison to patients without severe AKI (cortical mTT 16.1s vs 7.2s p=0.006). These differences are independent of both cardiac output (6.1l vs 5.7l, p=0.6) and renal artery blood flow (1.56l/min vs 1.81l/min, p=0.4). Biomarker data to identify perfusion abnormalities in AKI subphenotypes are awaited. Conclusion: Cortical hypoperfusion is detectable on admission to ICU using CEUS and identifies patients who will develop severe AKI. This paves the way for interventional study, individualizing renal resuscitation with vasoactive therapies.